HADIS QATL AL-MURTAD WA MAWAQIF AL-ULAMA' MINHU - Jannah, Shofiatul (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2022)
The Hadith of Killing Apostates and The Attitude of Scholars Toward it. This study discusses the hadith